Permisi, Bu! Acquisition of Indonesian Politeness for BIPA Learners - Wira Kurniawati (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
Politeness competence is essential for BIPA (Indonesian for Speakers of Other Languages) learners to communicate effectively within Indonesian sociocultural contexts. This study aims to identify (1) the practices of (im)politeness and the urgency of Indonesian politeness competence for BIPA learners, and (2) strategies for acquiring Indonesian politeness. Employing a qualitative design with naturalistic observation, the study examined learners’ interactions, errors, and politeness development over one semester. Data were collected through naturalistic and participatory observations of learners’ utterances, semi-structured interviews with teachers and learners, and questionnaires distributed to BIPA teachers. After orthographic transcription, data were analyzed by classifying pragmalinguistic and sociopragmatic aspects of politeness, alongside examining learner and teacher strategies in politeness acquisition. Findings reveal that occurrences of (im)politeness in learners’ speech demonstrate the importance of mastering this competence. Impoliteness commonly appeared through inappropriate personal pronoun selection, frequent use of informal registers, and excessive reliance on direct speech, resulting in ineffective communication, confusion, and reduced naturalness. Learners generally associated politeness with normative lexical markers, while register choice, the use of local linguistic elements, and indirect speech also influenced politeness meanings. Politeness acquisition was shaped by environmental factors, linguistic input, interaction and socialization, quality of exposure, and cross-cultural awareness. Teachers and peers served as systemic agents by providing explicit and implicit instruction, authentic situational input, active intervention, and cross-cultural reflective guidance through role-playing. These findings contribute to SLA sociopragmatic research and support holistic BIPA curriculum development.   Kompetensi kesantunan merupakan aspek penting yang harus dikuasai pemelajar BIPA agar dapat berkomunikasi secara efektif dalam konteks sosiokultural masyarakat Indonesia. Penelitian ini bertujuan untuk mengidentifikasi (1) praktik (ketidak)santunan dan urgensi kompetensi kesantunan bahasa Indonesia bagi pemelajar BIPA, serta (2) strategi pemerolehan kesantunan bahasa Indonesia oleh pemelajar BIPA. Penelitian ini menggunakan desain kualitatif dengan observasi naturalistik untuk mengkaji interaksi, kesalahan, dan perkembangan kesantunan pemelajar selama satu semester. Data dikumpulkan melalui observasi naturalistik dan partisipatif terhadap tuturan pemelajar, wawancara semi-terstruktur dengan pengajar dan pemelajar, serta angket yang diberikan kepada pengajar BIPA. Setelah ditranskripsikan secara ortografis, data dianalisis dengan mengklasifikasikan aspek pragmalinguistik dan sosiopragmatik kesantunan, sekaligus menelaah strategi pemerolehan kesantunan yang digunakan pemelajar dan strategi pengajaran yang diterapkan pengajar. Hasil penelitian menunjukkan bahwa kemunculan (ketidak)santunan dalam tuturan pemelajar menegaskan pentingnya penguasaan kompetensi ini. Ketidaksantunan umumnya tampak pada penggunaan pronomina persona yang kurang tepat, kecenderungan menggunakan ragam informal, dan ketergantungan berlebihan pada tuturan langsung, sehingga menyebabkan komunikasi kurang efektif, menimbulkan kebingungan, dan mengurangi kealamiahan berbahasa. Pemerolehan kesantunan dipengaruhi oleh lingkungan, masukan linguistik, interaksi dan sosialisasi, kualitas paparan, serta kesadaran lintas budaya. Guru dan teman sebaya berperan sebagai agen penting melalui pengajaran eksplisit dan implisit, pemberian masukan autentik, intervensi aktif, serta bimbingan reflektif lintas budaya melalui bermain peran. Temuan ini berkontribusi pada kajian pemerolehan sosiopragmatik bahasa kedua dan mendukung pengembangan kurikulum BIPA yang holistik.